Relapse versus reinfection with Clostridium difficile. - O'Neill, G. L. (Cambridge University Press, 1991)
Relapse of Clostridium difficile-associated diarrhoea occurs in 15-20% of patients; however, whether relapse is due to an endogenous source of the organism or reinfection from the environment remains unclear. Restriction enzyme analysis (REA) of chromosomal DNA was used to type multiple isolates from ten patients who had experienced apparent relapses. More than half the relapses were due to infection with a new strain of C. difficile. The remaining patients were infected with the same strain, but whether this strain was acquired from the environment or from endogenous sources could not be determined. Relapses with a different strain of C. difficile could occur if an individual harboured more than one strain in their gastrointestinal tract. To investigate this possibility ten other patients were assessed for carriage of multiple strains. Ten colonies from a primary culture plate from each patient were typed by REA and tested for their ability to produce cytotoxin. All isolates from the same patient were identical by both methods, indicating that multiple carriage of strains may be a rare event.